1971
DOI: 10.1161/01.res.29.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical Distribution of Renal Blood Flow in Hemorrhagic Shock in Dogs

Abstract: The effect of acute hypotensive hemorrhage on the intracortical distribution of renal blood flow was studied in anesthetized mongrel dogs with radioactive microspheres. In the early stages of shock, when carotid artery manipulation was avoided, outer cortical blood flow fell drastically and juxtamedullary flow was relatively well preserved. Carotid artery cannulation caused a redistribution of blood flow within the kidney even before hemorrhage, presumably by stimulating the carotid sinus reflex. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 22 publications
(34 reference statements)
2
19
0
Order By: Relevance
“…Recent studies from this and other laboratories have demonstrated that hemorrhagic hypotension is associ-ated with a marked decrease in the fractional distribution of renal cortical blood flow to outer cortical nephrons (1)(2)(3). This alteration in intrarenal hemodynamics may be related to one or more of the following changes known to occur during hemorrhage: (a) increased humoral release of norepinephrine (4), (b) increased humoral release of angiotensin (5), (c) enhanced adrenergic stimulation (6), and (d) diminished renal perfusion pressure.…”
Section: Introductionmentioning
confidence: 86%
“…Recent studies from this and other laboratories have demonstrated that hemorrhagic hypotension is associ-ated with a marked decrease in the fractional distribution of renal cortical blood flow to outer cortical nephrons (1)(2)(3). This alteration in intrarenal hemodynamics may be related to one or more of the following changes known to occur during hemorrhage: (a) increased humoral release of norepinephrine (4), (b) increased humoral release of angiotensin (5), (c) enhanced adrenergic stimulation (6), and (d) diminished renal perfusion pressure.…”
Section: Introductionmentioning
confidence: 86%
“…Logan, Jose, Eisner, Lilienfield & Slotkoff, 1971;Shirley, MacRae & Walker, 1991). A number of hormones whose release is stimulated by haemorrhage can account, at least in part, for the renal vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Logan e t al. (14) also demonstrate the effect of nonspecific stress on renal blood flow distribution. These authors showed that simple cannulation of the external carotid artery in dogs could result in a redistribution of intrarenal blood flow.…”
mentioning
confidence: 79%
“…Many conditions have been reported to result in a redistribution of renal blood flow. These include hemorrhage (14), acidosis (2), changes in hematocrit (17), and external perfusion of a kidney (I 9). Carriere and Biron (5) and Carriere and Friborg (6) have studied intrarenal blood flow distribution during angiotensin infusion.…”
mentioning
confidence: 99%